2009
DOI: 10.1159/000204227
|View full text |Cite
|
Sign up to set email alerts
|

11β-Hydroxysteroid Dehydrogenases Are Regulated during the Pulmonary Granulomatous Response to the Mycobacterial Glycolipid Trehalose-6,6′-Dimycolate

Abstract: Objective: Tuberculosis has a staggering influence on world health, resulting in nearly 2 million deaths per year. The influence of glucocorticoids during Mycobacterium tuberculosis infection has been under investigation for decades; however, the identity of mycobacterial factors and the mechanism by which glucocorticoids are tissue specifically regulated to influence immune function during acute granuloma formation are unknown. Methods: One factor implicated in initiating immunopathology during M. tuberculosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…In vitro studies show that BMM produce IL-6, TNF-␣ and IL-1 ␤ following TDM treatment [25] . These findings emulate the response seen in vivo, where pro-inflammatory cytokine production is strongly upregulated as early as one day after intravenous administration of TDM [16,33] . Relevant to this study, Welsh et al [16] demonstrated that cohesiveness of the granulomatous structure is lost when mice are unable to produce IL-6, even when TNF-␣ levels remain sufficiently elevated.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In vitro studies show that BMM produce IL-6, TNF-␣ and IL-1 ␤ following TDM treatment [25] . These findings emulate the response seen in vivo, where pro-inflammatory cytokine production is strongly upregulated as early as one day after intravenous administration of TDM [16,33] . Relevant to this study, Welsh et al [16] demonstrated that cohesiveness of the granulomatous structure is lost when mice are unable to produce IL-6, even when TNF-␣ levels remain sufficiently elevated.…”
Section: Discussionsupporting
confidence: 77%
“…Two micrograms of RNA was reverse transcribed and amplification of cDNA was assessed by the Taqman assay, using an ABI PRISM 7700 Sequence Detection System (Applied Biosystems, Foster City, Calif., USA) per previously published methods and sequences [16,33] . Changes in gene expression for 11 ␤ HSD1 and 11 ␤ HSD2 were analyzed by using the -2 ⌬ ⌬ C T method as described [34] , with ␤ -actin used for normalization of samples.…”
Section: Isolation and Purification Of Mrna Reverse Transcription Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Total lung RNA was isolated by homogenizing lung tissue in 1 ml of RNA-Bee (Tel-Test, Friendswood, TX), followed by addition of 0.1 ml of chloroform (Sigma) 28–30 . The samples were mixed, incubated on ice for 15 min, and centrifuged for 15 min at 13,000 rpm.…”
Section: Methodsmentioning
confidence: 99%